Genetic diversity of 16SrIII group phytoplasmas in Argentina. Predominance of subgroups 16SrIII-J and B and two new subgroups 16SrIII-W and X - Galdeano, Ernestina; Guzman, Fabiana; Fernandez, Franco Daniel; Conci, Luis Rogelio (Springer, 2018)
Twelve Argentinean 16SrIII (X-disease)-group phytoplasma strains were analyzed. Ten of them, detected in daisy (Bellis perennis), garlic (Allium sativum), ‘lagaña de perro’ (Caesalpinia gilliesii), periwinkle (Catharanthus roseus), ‘rama negra’ (Conyza bonariensis), ‘romerillo’ (Heterothalamus alienus), summer squash (Cucurbita maxima var. zapallito) and tomato (Solanum lycopersicum), are new phytoplasma strains while two strains, detected in garlic and China tree (Melia azedarach), have been previously described. The plants showed typical symptoms of phytoplasma diseases, such as leaf size reduction, proliferation, stunting and virescence. The identification and genetic diversity analysis of the phytoplasmas were performed based on 16S rDNA and ribosomal protein gene sequences. The classification into 16Sr groups and subgroups was established by actual and virtual RFLP analysis of the PCR products (R16F2/R16R2) compared with reference strains. According to the classification scheme, strains HetLL and ConWB-A and B represent two new subgroups 16SrIII-W and X, respectively. On the other hand, strains CatLL, TomLL and CaesLL are related to subgroup 16SrIII-B, and strains BellVir, TomRed, CucVir and GDIII-207 are related to subgroup 16SrIII-J. Ribosomal protein genes were amplified using primers rpF1/rpR1 and rpIIIF1/rpIIIR1. RFLP analysis performed with AluI, DraI and Tru1I (MseI isoschizomer) distinguished three new rp profiles within subgroup 16SrIII-B, one for subgroup 16SrIII-J, and one shared with strains of the new subgroups 16SrIII-W and X. The phylogenetic analysis based on 16S rDNA and ribosomal protein gene sequences confirmed the separation of HetLL and ConWB strains in two new subgroups and the close relatedness among subgroup J phytoplasmas, which have been detected only in South America.